Variation in the Neisseria lactamica porin, and its relationship to meningococcal PorB. - Bennett, J; Callaghan, M; Derrick, J; Maiden, M (2008)
One potential vaccine strategy in the fight against meningococcal disease involves the exploitation of outer-membrane components of Neisseria lactamica, a commensal bacterium closely related to the meningococcus, Neisseria meningitidis. Although N. lactamica shares many surface structures with the meningococcus, little is known about the antigenic diversity of this commensal bacterium or the antigenic relationships between N. lactamica and N. meningitidis. Here, the N. lactamica porin protein (Por) was examined and compared to the related PorB antigens of N. meningitidis, to investigate potential involvement in anti-meningococcal immunity. Relationships among porin sequences were determined using distance-based methods and F(ST), and maximum-likelihood analyses were used to compare the selection pressures acting on the encoded proteins. These analyses demonstrated that the N. lactamica porin was less diverse than meningococcal PorB and although it was subject to positive selection, this was not as strong as the positive selection pressures acting on the meningococcal porin. In addition, the N. lactamica porin gene sequences and the protein sequences of the loop regions predicted to be exposed to the human immune system were dissimilar to the corresponding sequences in the meningococcus. This suggests that N. lactamica Por, contrary to previous suggestions, may have limited involvement in the development of natural immunity to meningococcal disease and might not be effective as a meningococcal vaccine component.